Thermal mortar and preparation method thereof - GE HONG; ZHANG LONG; YI FEIZHOU; ZHAO YONGKUAN (2016)
The invention relates to the technical field of building mortar, and especially to a thermal mortar and a preparation method thereof. The thermal mortar has high heat-retaining property, freezing resistance, water-retaining property, compressive strength, and bonding strength by means of selecting components of the raw material and controlling and adjusting the weight ratio of components of the raw material, the phenomena of cracking, hollowing, cold wall, and condensing dew caused by change of the service environment of the thermal mortar are avoided, the energy consumption in the wall masonry process is reduced, and the efficacy of self-thermal insulation wall is reached by the thermal mortar, so that the energy can be saved over 70%. 本发明涉及建筑砂浆技术领域，尤其是种保温砂浆及其制备方法，通过对原料成分进行选取，并对原料成分的质量配比进行控制和调整，使得保温砂浆的保温性、抗冻性、保水性、抗压强度和粘结强度均较高，避免了由于保温砂浆使用环境的变化导致的开裂、空鼓、冷墙、结露水的现象，降低了墙体砌筑过程的能耗，使得保温砂浆能够实现自保温墙体的功效，进而达到节能70％以上。